2019
DOI: 10.18332/ejm/99544
|View full text |Cite
|
Sign up to set email alerts
|

Skilled health attendants’ knowledge and practice of pain management during labour in health care facilities in Ibadan, Nigeria

Abstract: INTRODUCTION Skilled health attendants occupy an important position in the management of women's pain during labour. Their professional goal is to ensure safety and minimum pain in labour. It has been revealed that nurse-midwives are deficient in knowledge and practice of pain management during labour. Hence, this study examined skilled health attendants' knowledge and practice of pain management in health care facilities in Ibadan, Nigeria. METHODS A cross-sectional design was used to collect data from 227 sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
4
5
3
Order By: Relevance
“…In this study, the main barriers for labouring women receiving pain relief included high patient flow, limited staff, a lack of knowledge and skill, no drugs available and no equipment available. This is in line with studies done in Nigeria, 28 , 29 Egypt 16 and the Amhara region. 18 These findings indicated that a weak healthcare system, weak facility organizations and limited distribution of resources limit access to maternal health services.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the main barriers for labouring women receiving pain relief included high patient flow, limited staff, a lack of knowledge and skill, no drugs available and no equipment available. This is in line with studies done in Nigeria, 28 , 29 Egypt 16 and the Amhara region. 18 These findings indicated that a weak healthcare system, weak facility organizations and limited distribution of resources limit access to maternal health services.…”
Section: Discussionsupporting
confidence: 92%
“…The finding of this study is lower than the studies conducted in Nigeria (48.4%), and Tigray Region, North Ethiopia (43.4%) [ 1 , 23 ] respectively. The discrepancy might be due to the difference in health facilities and sample size It was consistent with studies done in Bangladesh and Ghana where allowing laboring women to move freely, showing the patient how to bear down, allowing companionship, and massaging the back was the most applied non-pharmacologic pain relief methods [ 2 , 24 ]. But it was inconsistent with the study done in Nairobi [ 21 ].…”
Section: Discussionsupporting
confidence: 64%
“…This proportion of labour analgesia practice may be considered inadequate considering the tertiary health institution status and might allude to a lesser provision of pain relief in lower tier facilities in Kenya. These gures are, however, in contrast to similar studies conducted in Ibadan, Nigeria, at 34.4%, and Hawassa, Ethiopia, at 13.8% (10,16). The difference in practice might be due to the inclusion of different-tier public health care institutions in the preceding studies and, consequently, a difference in the knowledge and availability of resources.…”
Section: Discussioncontrasting
confidence: 57%